Analisa Perancangan Filter LCL Pada Penyearah PWM Satu Fasa Full Bridge - Hari Anna Lastya (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
Electronics devices need a direct current power supply although now only one alternating current power supply is available. Therefore, ac-dc converters which can convert an alternating current power supply to a direct current power supply will be needed. However, the use of this ac-dc converters will cause distortion in the form of current waves which are called harmonics. This harmonics can fault the work of the other electric devices which are attached to the same power source. Therefore, it is recommended that the harmonics generated by rectifiers should be under IEC 61000-3-2 standard. In this research will the reduction of harmonics by using LCL filter. At load of 2 kW, R of 5 ï—, L of 0,05 H at PWM rectifiers single phase full bridge with RL load produce the third harmonics current of 2.57 amperes, the installed LCL filter produces the third harmonics current of 1.26 amperes. According to IEC-61000-3-2 standard, the allowed third harmonics current is 2.3 amperes.